Observation of novel charge ordering and spin reorientation in perovskite oxide PbFeO3 - Xubin Ye (Nature Portfolio, 2021)
PbFeO3 is part of a family of lead based perovskites with many intriguing properties; however, difficulties in synthesis have hampered investigation. Here, the authors present a detailed study of the structure of PbFeO3 observing unique charge ordering and spin orientation among the constituent ions.